Can Organizational Identification Weaken the Negative Effects of Customer Bullying?—Testing the Moderating Effect of Organizational Identification - Huang, Haili; Yu, Shengxian; Peng, Pin (Frontiers in Psychology, 2022)
Customer bullying is a common phenomenon, causing short-term emotional distress or having long-term psychological impact on frontline employees of service enterprises, yielding either direct or indirect losses to service enterprises. While existing research has focused on the emotional and psychological impact of customer bullying on employees, little attention has been directed at the impact of customer bullying on negative employee behavior and internal mechanisms. In view of this, this paper draws on conservation of resources theory and discusses how and when customer bullying can lead to unethical behaviors. Furthermore, the mediating role of job insecurity and the moderating effect of organizational identification are analyzed. In study 1, 181 valid questionnaire data were collected at two time points, and regression data analysis was used to explore the effect of customer bullying on unethical behaviors through job insecurity. In study 2, 212 employees were recruited to investigate the moderating effect of organizational identification between customer bullying and unethical behaviors through a scenario experimental study. The results reveal that customer bullying is positively related to employees’ job insecurity and unethical behaviors. Job insecurity partially mediates the positive relationship between customer bullying and unethical behaviors. Further, the regression analysis results indicate that the direct effect of customer bullying on unethical behaviors is moderated by organizational identification. This study provides theoretical guidance for entrepreneurs to reduce both employee job insecurity and unethical behavior.